An Experiment in Wayfinding in a Subway Station Based on Eye Tracker Analytical Techniques for Universal and Age-Friendly Design - Shuxiang Wei; Dayu Xu; Jingze Wu; Qi Shen; Tong Nie (Buildings)
The complexity of subway station space can impact the efficiency of passenger navigation. The subway spatial environment is a key factor affecting indoor wayfinding for pedestrians; however, the research framework that examines how various environment factors influence pedestrians during different stages of wayfinding remains ambiguous. This study examines how environmental elements may affect users to varying degrees at different stages of wayfinding, which in turn affects their wayfinding efficiency, recording and analyzing the wayfinding performance and eye-tracking data of 32 participants. The findings reveal that different environment factors exert varying degrees of influence on pedestrians at different stages of wayfinding. Significantly, signage (p = 0.000) proves to have the most substantial impact on wayfinding, followed by stairs/escalators (p < 0.05), but the participants walked to the wrong platform in the TD2 scenario because they were guided by the Line 2 signs in front of the stairs/escalators. Thus, the influence of signage is not entirely positive. This study contributes to an understanding of the differences in the influence of environmental elements on wayfinding during different wayfinding stages, and provides suggestions for the spatial environmental design of subway stations and the improvement of wayfinding efficiency.